Inside pyroclastic surges - a characterisation of the flow behaviour, hazard impact mechanisms and sedimentation processes through large-scale experiments : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Earth Science at Massey University, Palmerston North, New Zealand - Brosch, Ermanno (Massey University, 2020)
Dilute pyroclastic density currents (or pyroclastic surges) are frequently occurring and highly dangerous volcanic flows generated during explosive volcanic eruptions. These fast and ground-hugging flows of hot volcanic particles and gas swiftly sweep across landscapes to cause significant risk to life and infrastructure at many volcanoes globally. Understanding the flow dynamics of pyroclastic surges, and developing a quantitative understanding of the mechanisms behind their hazard impacts, are thus important requisites for the development and testing of robust hazard mitigation strategies. Despite strong progress through field, theoretical, laboratory and numerical approaches during the past 50 years, the understanding of the flow and hazard behaviour of pyroclastic surges is still highly fragmentary. An important reason behind current gaps in knowledge stems from the hostile nature of these currents, which, to date, has prevented any direct observations and internal measurements. This leaves many theories behind flow and hazard models untested and un-validated. Over the past ten years, large-scale experiments have provided a novel approach to generate the missing ‘view’ inside pyroclastic density currents. While recent experiments have improved the understanding of the internal flow behaviour of dense pyroclastic density currents, comparable large-scale experimental studies for pyroclastic surges remain outstanding. This thesis describes the first systematic series of large-scale experiments that aimed to obtaining detailed measurements of the dangerous interior conditions of pyroclastic surges. Conducted at the international eruption simulator facility PELE (the Pyroclastic flow Eruption Large-scale Experiment), this study aimed to provide answers to the following three research questions: What are the flow-internal processes that cause the extreme destruction potential of pyroclastic surges? What is the detailed internal structure of pyroclastic surges? What are the particle-transport and sedimentation processes occurring in the basal region of dilute PDCs? Through the development of new measurement techniques and the refinement of existing set-up approaches, a systematic series of experiments were completed, which provided comprehensive datasets of dilute PDC analogues. The main results and implications of this research are as follows. Direct measurements of the internal velocity and density structure inside experimental flows show that turbulence is an important driver of the destructiveness of pyroclastic density currents. The effects of turbulence manifest themselves through three cumulative mechanisms. First, most of the flow energy becomes focussed into large eddies whose turbulent excursions generate destruction-causing dynamic pressures that exceed traditionally estimated mean values manifold. Second, self-developed pulsing inside flows, associated with the propagation of large coherent turbulence structures, leads to high dynamic pressures, propagating and perpetuating downstream. Third, the characteristic frequencies associated with large eddy motion are able to excite resonance in large buildings. The characterisation of gas-particle interactions inside the dynamically and kinematically scaled experimental pyroclastic surges revealed that commonly assumed near-homogeneous coupling between particles and gas is the exception, while strong to intermediate feedback loops between gas and solid phases are omnipresent throughout most of the evolving flow. This leads to interesting mesoscale turbulence effects, which are here shown to modify and control the evolving vertical flow stratification, the spatiotemporally varying deposition mechanisms, and the generation of turbulence in addition to the typically assumed shear and buoyancy processes. The spatially variable velocity of the leading front of the experimental surges is here demonstrated to behave differently to aqueous particle-laden gravity currents. The propagation of flow-internal pulses inside the highly turbulent gravity currents is a key mechanism in determining the flow runout and consequent hazard characteristics. The deposits of the experimental pyroclastic surges are here shown to have strong similarities to real-world deposits. Simultaneous measurements of the evolving structure of the lower flow boundary and the accreting deposit add complexity to our current qualitative view of the sediment transport and deposition mechanisms inside pyroclastic surges. The occurrence of mesoscale turbulence modifies particle supply into the lower flow boundary and, through the rapid passage of large-eddy passages in this region, gives rise to dynamic changes between a range of bedload transport processes and deposition rates. A correlation of the contribution of the different regions of the experimental surge to the spatially and temporally evolving deposit provides new insights in to how real-world deposits originate and how best to sample them to characterise the behaviour of past PDC-forming eruptions. Parts of the experimental datasets obtained during this research form the first international benchmark case to test, validate and compare the current range of numerical dilute PDC flow and hazard models.
Keywords: Volcanic ash, tuff, etc.; Density currents; Fluid dynamics; Mathematical models; Volcanic hazard analysis; 370512 Volcanology